Improving concept development success rates by effective redesign of internal collaborative processes - Pedrinho, A.; Vilas-Boas, J.; Möhring, M.; Stich, C. (Proceedings of 27th EurOMA, 2020)
This applied research introduces a technique to increase projects’ success concerning future concepts in high-tech companies. Research questions, “how to select, develop and evaluate future business opportunities”, were addressed by an innovative framework and financial analysis best practices. Scope is delimited to the planning stage of New Product Development (NPD) process to transform opportunities into structured justified projects. An exploratory qualitative case study was chosen to conduct empirical, abductive research, identifying as failure root causes: no inter-departmental support/communication, inadequate process handover. Results discussion confirmed the framework, upgraded by collaborative knowledge-diffusion management, as a NPD research contribution.